2014
DOI: 10.1371/journal.pone.0099412
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of CD24 as a Cancer Stem Cell Marker in Human Nasopharyngeal Carcinoma

Abstract: Cancer stem cells (CSCs) represent a unique sub-population of tumor cells with the ability to initiate tumor growth and sustain self-renewal. Although CSC biomarkers have been described for various tumors, only a few markers have been identified for nasopharyngeal carcinoma (NPC). In this study, we show that CD24+ cells isolated from human NPC cell lines express stem cell genes (Sox2, Oct4, Nanog, Bmi-1, and Rex-1), and show activation of the Wnt/β-catenin signaling pathway. CD24+ cells possess typical CSC cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 59 publications
2
39
0
Order By: Relevance
“…The lower expressions of c-myc, Nanog, Oct3/4, Sox2, and EpCAM in β-catenin-silenced cells suggested that the production of CSC was suppressed. The enrichment of Sox2 in CSC-like population in NPC has already been reported, and Sox2 has also found to be involved in regulating the growth of the CSC-like population in NPC [4,35]. In the present study, we demonstrated that silencing β-catenin would inversely influence the expression of Sox2 both in vitro and in vivo.…”
Section: β-Catenin Is Necessary For Maintaining Characteristics Of Cssupporting
confidence: 81%
“…The lower expressions of c-myc, Nanog, Oct3/4, Sox2, and EpCAM in β-catenin-silenced cells suggested that the production of CSC was suppressed. The enrichment of Sox2 in CSC-like population in NPC has already been reported, and Sox2 has also found to be involved in regulating the growth of the CSC-like population in NPC [4,35]. In the present study, we demonstrated that silencing β-catenin would inversely influence the expression of Sox2 both in vitro and in vivo.…”
Section: β-Catenin Is Necessary For Maintaining Characteristics Of Cssupporting
confidence: 81%
“…In human nasopharyngeal carcinoma cell lines, cells with higher CD24 C expression have increased growth and tumor sphere formation in vitro. 36 While previous studies look at the role of CD24 in the tumors, our investigation turned to analysis of CD24 in the immune system in regulation of tumor control.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the sorting methods of CSCs include flow cytometry based on special cell surface markers, the side population cell sorting technique, tumor sphere culturing and the ALDEFLUOR™ assay (6)(7)(8)(9). Previous studies have identified the CSCs from colon, breast and glioblastoma cancer, as well as other cancer cell lines, using the sphere culturing method (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%